Flaxseed- and chia seed-derived protein hydrolysates exhibiting enhanced in vitro antidiabetic, anti-obesity, and antioxidant properties - Mudgil, Priti; Ajayi, Feyisola Fisayo; Alkaabi, Amani; Alsubousi, Maitha; Singh, Brij Pal; Maqsood, Sajid (Frontiers in Sustainable Food Systems, 2023)
This study investigated in vitro antidiabetic, anti-obesity, and antioxidant activities of chia seed protein hydrolysates (CSPHs) and flaxseed protein hydrolysates (FSPHs) generated using three food-grade proteases at the hydrolysis at intervals of 120 min for 6 h. The inhibitory potentials of CSPHs and FSPHs on the enzymatic biomarkers related to diabetes (α-glucosidase and DPP-4) and obesity (pancreatic lipase and cholesteryl esterase) were determined. The antioxidant capacity of CSPHs and FSPHs was also assessed using ABTS, DPPH, and FRAP antioxidant assays. Increasing the proteolytic reaction time was shown to significantly increase the degree of hydrolysis values of CSPHs and FSPHs. Protein hydrolysates resulted in higher inhibitory potential against enzymatic biomarkers related to metabolic diseases (diabetes and obesity) as well as higher antioxidant activities compared with undigested proteins. Overall, the lowest IC50 inhibition values demonstrated in DPP-IV were observed by alcalase-catalyzed CSPH at 6 h (IC50 = 272.17 μg/mL) and bromelain-catalyzed FSPH at 6 h (IC50 = 338.70 μg/mL). The strongest inhibition of pancreatic lipase was observed in bromelain-catalyzed hydrolysates (IC50 = 292.43 μg/mL and IC50 = 307.62 μg/mL for CSPH and FSPH, respectively) after 6 h. These findings indicate that CSPHs and FSPHs exhibited enhanced antidiabetic, anti-obesity, and antioxidant properties. Therefore, these hydrolysates can be successfully used for their applications in the development of functional foods.